Experimental comparison of protective characteristics of enalapril and trimetazidine in diabetic nephropathy. (September 2014) - Karadeniz, Tugba; Cavusoğlu, Turker; Turkmen, Engin; Uyanıkgil, Yigit; Karadeniz, Muammer; Akdemir, Ovunc; Tuglu, M. Ibrahim; Ates, Utku; Erbas, Oytun
Abstract Hyperglycemia, hypertension, dyslipidemia, and inflammation have been proposed to account for the development of nephropathy in diabetic subjects. The beneficial effects of enalapril on diabetic nephropathy are known. However, the effects of trimetazidine (TMZ) are still unknown. We aimed at comparing the effects of the enalapril and TMZ treatment on fibronectin expression, inducible nitric oxide synthase expression, urine proteinuria, blood glucose and glomerular, and mesangial structures of kidney in rats that take streptozotocin (STZ). In this study, 32 male Sprague–Dawley albino mature rats of 8 weeks, weighing 200–220 g were used. Diabetes was induced by intraperitoneal injection of STZ (60 mg/kg) for 24 rats. We made four groups (Group 1: control, non-diabetic rats (n = 8), Group 2: diabetes, without treatment (n = 8), Group 3: diabetes treatment with enalapril (n = 8), Group 4: diabetes treatment with TMZ (n = 8). The positive effects of renal tissue and tubules in the mesangium immunohistochemical were shown in TMZ receiving rat groups. These positive effects were in parallel with the reduction in fibronectin and I-NOS expression and reduction in the proteinuria. TMZ and enalapril treatment of diabetic rats and renal parenchyma in this study are shown to have positive effects on the different levels.